A kind of preparation method of sorbitol
By performing multi-step treatment of activated carbon to prepare high-efficiency catalysts, the problems of degraded catalyst performance and poor storage resistance in the prior art are solved, and sorbitol preparation with high conversion and high yield is achieved.
Patent Information
- Application Number
- CN202411252022.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-09-09
AI Technical Summary
In the existing sorbitol preparation method, the conversion and yield of the catalyst are low, the catalytic performance of the catalyst weakens after multiple recovery, and the storage resistance is poor.
By alkaline irrigating, thiolation, oxidation and loading treatment of activated carbon, sulfonated activated carbon with high dispersion and uniform loading was prepared, and combined with functionalized silica to form an efficient catalyst.
The conversion rate of glucose and sorbitol yield were improved. The catalyst still maintained good catalytic performance after multiple recovery and ultraviolet irradiation, and the storage resistance performance was significantly improved.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sorbitol, and particularly relates to a method for preparing sorbitol. Background Art
[0002] Sorbitol, also known as sorbitol, is the raw material for the production of vitamin C. It can also be used as a raw material for industrial surfactants. It can also be used as a nutritional sweetener, wetting agent, chelating agent and stabilizer. It is widely used in the fields of medicine, food, chemical industry, etc.
[0003] At present, the methods for synthesizing sorbitol mainly include electrolysis, microbial fermentation and catalytic hydrogenation. The electrolysis method is to produce sorbitol by electroreduction of glucose, which consumes huge amount of electricity and limits the application of electrolysis reduction technology. The microbial fermentation method is to ferment glucose with specific enzymes or microorganisms as media, but the enzymes or microorganisms are expensive, and the microorganisms, raw materials and products after the reaction are difficult to separate, and the enzymes and microorganisms cannot be recycled.
[0004] The catalytic hydrogenation method uses glucose, starch, etc. as raw materials to prepare sorbitol through kettle hydrogenation. Generally, a glucose solution is mixed with hydrogen in a high-pressure reactor, and the catalytic action of the catalyst is used to control the reaction temperature and pressure to produce a sorbitol liquid that meets the standards. In the entire reaction process, the catalyst is the key, and platinum, ruthenium, and nickel are mostly used as the central metal, loaded on carriers such as activated carbon and metal oxides.
[0005] CN118384898A discloses a catalyst for preparing sorbitol and a method for preparing sorbitol, specifically disclosing the use of activated carbon as a carrier, adding the carrier into a nitric acid solution for treatment, then adding the carrier into a soluble salt solution of ruthenium trichloride trihydrate and copper, impregnating and drying, and finally reducing the catalyst product under a hydrogen atmosphere, mixing the catalyst product with a glucose solution and placing it in a reaction container, controlling a certain pressure and temperature for a hydrogenation reaction, and obtaining sorbitol;
[0006] The method of the patent is used to prepare sorbitol, with a conversion rate of 85.7% and a yield of 73.2%. However, the method still has the defects of low conversion rate and yield, and the catalytic performance of the catalyst obtained is weakened after multiple recycling and application, which affects the hydrogenation reaction and greatly reduces the conversion rate and yield.
[0007] The applicant also found that the catalyst prepared by the prior art has poor storage resistance. After the catalyst is placed for a period of time, the catalytic performance is significantly reduced, which also affects the reaction. Summary of the invention
[0008] In order to solve the above technical problems of the prior art, the present invention provides a method for preparing sorbitol, which has high glucose conversion rate and high product yield, and the catalyst still has good catalytic performance and good storage resistance after being recycled and reused for many times.
[0009] In view of the above technical problems, the present invention adopts the following technical solutions:
[0010] A method for preparing sorbitol includes alkali leaching activated carbon, preparing mercapto activated carbon, oxidation, loading and reaction steps, and the specific operations are as follows:
[0011] 1. Alkali leaching activated carbon
[0012] The activated carbon is placed in a sodium hydroxide solution for soaking at a temperature of 90-94°C for a soaking time of 11-13 hours. After the soaking is completed, the activated carbon is filtered, washed and dried to obtain alkali-leached activated carbon.
[0013] The particle size of the activated carbon is 220-240nm, and the specific surface area is 605-614m 2 / g;
[0014] The mass concentration of the sodium hydroxide solution is 14-17%;
[0015] The mass ratio of the activated carbon to the sodium hydroxide solution is 10-14:95-123.
[0016] 2. Preparation of thiol activated carbon
[0017] The alkali-leached activated carbon is placed in a sealed container, an ethanol solution and a pretreatment agent are introduced, the temperature is raised to 40-44°C at a rate of 1.4-1.6°C / min, and stirred for 23-28min, and then the temperature is raised to 60-64°C at a rate of 0.8-1.0°C / min, and stirred for 16-20min. After the soaking, 3-mercaptopropyltriethoxysilane is added, and the temperature is raised to 73-77°C at a rate of 0.4-0.6°C / min for stirring reaction. The reaction time is 9.8-10.3h, and the stirring speed is 212-226rpm. After the reaction is completed, the thiol activated carbon is filtered, washed, and dried to obtain the thiol activated carbon;
[0018] The mass concentration of the ethanol solution is 42-45%;
[0019] The pretreatment agent is a mixture of polyethylene glycol monolaurate, dimethyl silicone oil and octadecyl trimethyl ammonium bromide, and the mass ratio of the polyethylene glycol monolaurate, dimethyl silicone oil and octadecyl trimethyl ammonium bromide is 1.4-1.6:0.6-0.8:0.8-1.2;
[0020] The mass ratio of the alkali-leached activated carbon, the ethanol solution, the pretreatment agent, and 3-mercaptopropyltriethoxysilane is 8.2-8.6:95-100:1.3-1.5:0.8-1.0.
[0021] 3. Oxidation
[0022] The sulfhydryl activated carbon and the hydrogen peroxide solution are mixed and ultrasonically treated, the ultrasonic time is 13-18 minutes, the ultrasonic power is 140-154W, the ultrasonic frequency is 43-47kHz, and the stirring is performed after the ultrasonic treatment, the stirring time is 23-25 hours, and the stirring speed is 413-425rpm. After the stirring is completed, the mixture is dried at 78-82°C for 6.7-7.2 hours to obtain the sulfonated activated carbon;
[0023] The mass concentration of the hydrogen peroxide solution is 30-34%;
[0024] The mass ratio of the mercapto activated carbon to the hydrogen peroxide solution is 7.3-7.7:52-56.
[0025] 4. Load
[0026] Add nickel nitrate hexahydrate to deionized water, stir evenly, then add sulfonated activated carbon and sodium dodecylbenzene sulfonate, stir at 393-406 rpm for 7.8-8.2 hours, add functionalized silica after stirring, heat to 51-55° C. and stir for 2.8-3.2 hours, filter, wash and dry, place under hydrogen atmosphere, heat to 265-275° C. at a rate of 2.6-3.4° C. / min, keep at 265-275° C. for 18-22 minutes, then heat to 405-415° C. at a rate of 1.7-2.3° C. / min, keep at 405-415° C. for 4.4-4.6 hours, and after the heat preservation, naturally return to room temperature to obtain a catalyst;
[0027] The mass volume ratio of the deionized water, nickel nitrate hexahydrate, sulfonated activated carbon, sodium dodecylbenzene sulfonate, and functionalized silica is 73-77 mL: 1.8-2.2 g: 3.2-3.5 g: 0.07-0.09 g: 1.8-2.2 g;
[0028] The preparation method of the functionalized silica comprises the following steps: placing silica in a sealed container, introducing a 36-40wt% ethanol solution, adding triethanolamine dodecyl sulfate for ball milling, wherein the ball milling time is 23-27min, the ball milling speed is 113-125rpm, and the ball-to-material ratio is 3-5:1; after the ball milling, adding fatty acid polyoxyethylene ester and 3-aminopropyltrimethoxysilane, raising the temperature to 72-76°C, and performing ball milling, wherein the ball milling time is 33-37min, the ball milling speed is 204-215rpm, and the ball-to-material ratio is 4-6:1; after the ball milling, stirring and reacting for 6.3-6.7h; after the stirring and reacting, filtering, washing, and drying are performed to obtain the functionalized silica;
[0029] The particle size of the silicon dioxide is 205-215 nm;
[0030] The mass ratio of the silicon dioxide, the ethanol solution, the triethanolamine dodecyl sulfate, the polyoxyethylene fatty acid ester and the 3-aminopropyltrimethoxysilane is 10.7-11.0:95-100:0.8-1.2:0.6-0.8:1.0-1.3.
[0031] 5. React
[0032] Add 14-16wt% glucose solution and catalyst into the reaction container, replace the gas in the reaction container with hydrogen for 3 times, then introduce hydrogen for stirring reaction, control the reaction pressure to 3.8-4.2MPa, the stirring speed to 590-607rpm, the reaction time to 3.9-4.2h, the reaction temperature to 120-125°C, obtain the reaction liquid after the reaction, cool it, filter it, and sample and analyze the filtrate;
[0033] The mass volume ratio of the 14-16wt% glucose solution and the catalyst is 195-204mL:0.57-0.60g.
[0034] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0035] 1. The present invention performs thiol treatment on activated carbon, wherein the pretreatment agent mainly plays a role in surface dispersion, reduces the agglomeration of activated carbon, and enhances the dispersion performance. Then, the activated carbon is treated with a silane coupling agent so that the surface of the activated carbon contains thiol groups. After oxidation, the thiol groups are fully oxidized to sulfonic acid groups. In the loading step, the porous structure of the activated carbon can load the metal components, and the dispersion degree of the metal components on the sulfonated activated carbon is high, and the loading is more uniform, so that the catalytic activity can be better exerted. Functionalized silica is also added in the complex step. The functionalized silica obtained by specific dispersion treatment and silane treatment is rich in amino groups and And it is presented as separately dispersed particles. Under the action of sodium dodecylbenzene sulfonate, the amino groups of the functionalized silica can effectively interact with the sulfonic acid groups of the sulfonated activated carbon to form acid-base hydrogen bonds, so that a layer of silica is coated on the surface of the sulfonated activated carbon. The amino groups of the functionalized silica have good binding properties with the reactant glucose, which promotes the full progress of the reaction. The sulfonic acid group and the amino group have good compatibility in the glucose solution, which enhances the catalytic stability of the catalyst and reduces the loss of metal components during the reaction, so that the catalyst still has good catalytic performance after multiple recycling and strong ultraviolet irradiation.
[0036] 2. Sorbitol was prepared by the method of the present invention. After sampling and analyzing the filtrate, the conversion rate of glucose was 99.51-99.75%, and the yield of sorbitol was 94.25-94.73%;
[0037] 3. The catalyst prepared by the present invention was recycled and reused for 26 times. When the catalyst was recycled and reused for the 26th time, the conversion rate of glucose was 94.34-96.16%, and the yield of sorbitol was 87.65-89.52%;
[0038] 4. The catalyst prepared by the present invention is recovered and reused, and placed at an intensity of 600W / m 2 The mixture was irradiated under ultraviolet light for 10 days and then the reaction step was carried out. The conversion rate of glucose was 95.73-97.26%, and the yield of sorbitol was 89.25-91.22%. DETAILED DESCRIPTION
[0039] In order to more clearly understand the technical features, purposes and effects of the present invention, specific embodiments of the present invention are now described.
[0040] Example 1
[0041] 1. Alkali leaching activated carbon
[0042] 12g of activated carbon was placed in 110g of sodium hydroxide solution for soaking at 92°C for 12h. After the soaking, it was filtered, washed and dried to obtain alkali-leached activated carbon.
[0043] The particle size of the activated carbon is 230nm and the specific surface area is 610m 2 / g;
[0044] The mass concentration of the sodium hydroxide solution is 15%.
[0045] 2. Preparation of thiol activated carbon
[0046] 8.4 g of alkali-leached activated carbon was placed in a sealed container, 97 g of ethanol solution and 1.4 g of pretreatment agent were introduced, the temperature was raised to 42 ° C at a rate of 1.5 ° C / min, stirred for 25 min, and then raised to 62 ° C at a rate of 0.9 ° C / min, stirred for 17 min, 0.9 g of 3-mercaptopropyltriethoxysilane was added after the soaking, the temperature was raised to 75 ° C at a rate of 0.5 ° C / min for stirring reaction, the reaction time was 10 h, the stirring speed was 220 rpm, and after the reaction was completed, the mercapto activated carbon was filtered, washed and dried to obtain;
[0047] The mass concentration of the ethanol solution is 43%;
[0048] The pretreatment agent is a mixture of polyethylene glycol monolaurate, dimethyl silicone oil and octadecyl trimethyl ammonium bromide, and the mass ratio of the polyethylene glycol monolaurate, dimethyl silicone oil and octadecyl trimethyl ammonium bromide is 1.5:0.7:1.0.
[0049] 3. Oxidation
[0050] 7.5 g of mercapto activated carbon was mixed with 54 g of hydrogen peroxide solution, and subjected to ultrasonic treatment. The ultrasonic time was 15 min, the ultrasonic power was 148 W, and the ultrasonic frequency was 45 kHz. After the ultrasonic treatment, the mixture was stirred for 24 h at a stirring speed of 420 rpm. After the stirring was completed, the mixture was dried at 80 ° C for 7 h to obtain sulfonated activated carbon.
[0051] The mass concentration of the hydrogen peroxide solution is 32%.
[0052] 4. Load
[0053] 2.0 g of nickel nitrate hexahydrate was added to 75 mL of deionized water, and after stirring, 3.4 g of sulfonated activated carbon and 0.08 g of sodium dodecylbenzene sulfonate were added, and the mixture was stirred at 400 rpm for 8 h. After the stirring was completed, 2.0 g of functionalized silica was added, and the mixture was heated to 53 ° C and stirred for 3.0 h. After filtering, washing and drying, the mixture was placed in a hydrogen atmosphere, heated to 270 ° C at a rate of 3.0 ° C / min, and kept at 270 ° C for 20 min, and then heated to 410 ° C at a rate of 2.0 ° C / min, and kept at 410 ° C for 4.5 h. After the insulation was completed, the mixture was naturally restored to room temperature to obtain a catalyst;
[0054] The preparation method of the functionalized silica comprises placing silica in a sealed container, introducing a 37 wt % ethanol solution, adding triethanolamine dodecyl sulfate for ball milling, wherein the ball milling time is 25 min, the ball milling speed is 120 rpm, and the ball-to-material ratio is 4:1. After the ball milling, fatty acid polyoxyethylene ester and 3-aminopropyltrimethoxysilane are added, and the temperature is increased to 74° C., and the ball milling is performed, wherein the ball milling time is 35 min, the ball milling speed is 210 rpm, and the ball-to-material ratio is 5:1. After the ball milling is completed, stirring and reacting is performed for 6.5 h. After the stirring and reaction is completed, filtering, washing, and drying are performed to obtain the functionalized silica.
[0055] The particle size of the silicon dioxide is 210 nm;
[0056] The mass ratio of the silicon dioxide, the ethanol solution, triethanolamine dodecyl sulfate, polyoxyethylene fatty acid ester, and 3-aminopropyltrimethoxysilane is 10.8:97:1.0:0.7:1.1.
[0057] 5. React
[0058] Add 200 mL of 15 wt% glucose solution and 0.58 g of catalyst to the reaction container, replace the gas in the reaction container with hydrogen three times, and then introduce hydrogen for stirring reaction. Control the reaction pressure to 4.0 MPa, the stirring speed to 600 rpm, the reaction time to 4 h, and the reaction temperature to 123 ° C. After the reaction is completed, the reaction liquid is obtained, cooled and filtered, and the filtrate is sampled and analyzed.
[0059] Sorbitol was prepared by the method of Example 1. After sampling and analysis of the filtrate, the conversion rate of glucose was 99.75%, and the yield of sorbitol was 94.73%.
[0060] Example 2
[0061] 1. Alkali leaching activated carbon
[0062] 10g of activated carbon was placed in 95g of sodium hydroxide solution for soaking at 90°C for 11h. After the soaking, it was filtered, washed and dried to obtain alkali-leached activated carbon.
[0063] The particle size of the activated carbon is 220nm and the specific surface area is 605m 2 / g;
[0064] The mass concentration of the sodium hydroxide solution is 14%.
[0065] 2. Preparation of thiol activated carbon
[0066] 8.2g of alkali-leached activated carbon was placed in a sealed container, 95g of ethanol solution and 1.3g of pretreatment agent were introduced, the temperature was raised to 40°C at a rate of 1.4°C / min, stirred for 23min, then raised to 60°C at a rate of 0.8°C / min, stirred for 16min, 0.8g of 3-mercaptopropyltriethoxysilane was added after the soaking, the temperature was raised to 73°C at a rate of 0.4°C / min for stirring reaction, the reaction time was 9.8h, the stirring speed was 212rpm, after the reaction was completed, the mixture was filtered, washed and dried to obtain mercapto activated carbon;
[0067] The mass concentration of the ethanol solution is 42%;
[0068] The pretreatment agent is a mixture of polyethylene glycol monolaurate, dimethyl silicone oil and octadecyl trimethyl ammonium bromide, and the mass ratio of the polyethylene glycol monolaurate, dimethyl silicone oil and octadecyl trimethyl ammonium bromide is 1.4:0.6:0.8.
[0069] 3. Oxidation
[0070] 7.3 g of mercapto activated carbon was mixed with 52 g of hydrogen peroxide solution, and ultrasonic treatment was performed. The ultrasonic time was 13 min, the ultrasonic power was 140 W, and the ultrasonic frequency was 43 kHz. After the ultrasonic treatment, stirring was performed. The stirring time was 23 h and the stirring speed was 413 rpm. After the stirring was completed, the mixture was dried at 78 ° C for 6.7 h to obtain sulfonated activated carbon.
[0071] The mass concentration of the hydrogen peroxide solution is 30%.
[0072] 4. Load
[0073] 1.8 g of nickel nitrate hexahydrate was added to 73 mL of deionized water, and after stirring, 3.2 g of sulfonated activated carbon and 0.07 g of sodium dodecylbenzene sulfonate were added, and the mixture was stirred at 393 rpm for 7.8 h. After the stirring was completed, 1.8 g of functionalized silica was added, and the mixture was heated to 51° C. and stirred for 2.8 h. After filtering, washing, and drying, the mixture was placed in a hydrogen atmosphere, and the temperature was increased to 265° C. at a rate of 2.6° C. / min, and kept at 265° C. for 18 min, and then the temperature was increased to 405° C. at a rate of 1.7° C. / min, and kept at 405° C. for 4.4 h. After the insulation was completed, the mixture was naturally restored to room temperature to obtain a catalyst.
[0074] The preparation method of the functionalized silica comprises placing silica in a sealed container, introducing a 36 wt % ethanol solution, adding triethanolamine dodecyl sulfate for ball milling, wherein the ball milling time is 23 min, the ball milling speed is 113 rpm, and the ball-to-material ratio is 3:1. After the ball milling, fatty acid polyoxyethylene ester and 3-aminopropyltrimethoxysilane are added, and the temperature is increased to 72° C. for ball milling, wherein the ball milling time is 33 min, the ball milling speed is 204 rpm, and the ball-to-material ratio is 4:1. After the ball milling, stirring and reacting for 6.3 h, after the stirring and reaction, filtering, washing, and drying are performed to obtain the functionalized silica.
[0075] The particle size of the silicon dioxide is 205 nm;
[0076] The mass ratio of the silicon dioxide, the ethanol solution, triethanolamine dodecyl sulfate, polyoxyethylene fatty acid ester, and 3-aminopropyltrimethoxysilane is 10.7:95:0.8:0.6:1.0.
[0077] 5. React
[0078] Add 195mL of 14wt% glucose solution and 0.57g of catalyst to the reaction container, replace the gas in the reaction container with hydrogen three times, and then introduce hydrogen for stirring reaction. Control the reaction pressure to 3.8MPa, the stirring speed to 590rpm, the reaction time to 3.9h, and the reaction temperature to 120°C. After the reaction, obtain the reaction liquid, cool it, filter it, and sample the filtrate for analysis.
[0079] Sorbitol was prepared by the method of Example 2. After sampling and analysis of the filtrate, the conversion rate of glucose was 99.51% and the yield of sorbitol was 94.25%.
[0080] Example 3
[0081] 1. Alkali leaching activated carbon
[0082] 14g of activated carbon was placed in 123g of sodium hydroxide solution for soaking at 94°C for 13h. After the soaking, it was filtered, washed and dried to obtain alkali-leached activated carbon.
[0083] The particle size of the activated carbon is 240nm and the specific surface area is 614m 2 / g;
[0084] The mass concentration of the sodium hydroxide solution is 17%.
[0085] 2. Preparation of thiol activated carbon
[0086] 8.6 g of alkali-leached activated carbon was placed in a sealed container, 100 g of ethanol solution and 1.5 g of pretreatment agent were introduced, the temperature was raised to 44 ° C at a rate of 1.6 ° C / min, stirred for 28 min, and then raised to 64 ° C at a rate of 1.0 ° C / min, stirred for 20 min, 1.0 g of 3-mercaptopropyltriethoxysilane was added after the soaking, the temperature was raised to 77 ° C at a rate of 0.6 ° C / min for stirring reaction, the reaction time was 10.3 h, the stirring speed was 226 rpm, and after the reaction was completed, the mercapto activated carbon was filtered, washed and dried to obtain;
[0087] The mass concentration of the ethanol solution is 45%;
[0088] The pretreatment agent is a mixture of polyethylene glycol monolaurate, dimethyl silicone oil and octadecyl trimethyl ammonium bromide, and the mass ratio of the polyethylene glycol monolaurate, dimethyl silicone oil and octadecyl trimethyl ammonium bromide is 1.6:0.8:1.2.
[0089] 3. Oxidation
[0090] 7.7 g of mercapto activated carbon was mixed with 56 g of hydrogen peroxide solution, and subjected to ultrasonic treatment. The ultrasonic time was 18 min, the ultrasonic power was 154 W, and the ultrasonic frequency was 47 kHz. After the ultrasonic treatment, the mixture was stirred for 25 h at a stirring speed of 425 rpm. After the stirring was completed, the mixture was dried at 82 ° C for 7.2 h to obtain sulfonated activated carbon.
[0091] The mass concentration of the hydrogen peroxide solution is 34%.
[0092] 4. Load
[0093] 2.2 g of nickel nitrate hexahydrate was added to 77 mL of deionized water, and after stirring, 3.5 g of sulfonated activated carbon and 0.09 g of sodium dodecylbenzene sulfonate were added, and the mixture was stirred at 406 rpm for 8.2 h. After the stirring was completed, 2.2 g of functionalized silica was added, and the mixture was heated to 55 ° C and stirred for 3.2 h. After filtering, washing and drying, the mixture was placed in a hydrogen atmosphere, and the temperature was increased to 275 ° C at a rate of 3.4 ° C / min, and kept at 275 ° C for 22 min, and then the temperature was increased to 415 ° C at a rate of 2.3 ° C / min, and kept at 415 ° C for 4.6 h. After the insulation was completed, the mixture was naturally restored to room temperature to obtain a catalyst;
[0094] The preparation method of the functionalized silica comprises placing silica in a sealed container, introducing a 40 wt% ethanol solution, adding triethanolamine dodecyl sulfate for ball milling, wherein the ball milling time is 27 minutes, the ball milling speed is 125 rpm, and the ball-to-material ratio is 5:1. After the ball milling, fatty acid polyoxyethylene ester and 3-aminopropyltrimethoxysilane are added, and the temperature is increased to 76° C. for ball milling, wherein the ball milling time is 37 minutes, the ball milling speed is 215 rpm, and the ball-to-material ratio is 6:1. After the ball milling, stirring and reacting for 6.7 hours, filtering, washing, and drying are performed to obtain the functionalized silica.
[0095] The particle size of the silicon dioxide is 215 nm;
[0096] The mass ratio of the silicon dioxide, the ethanol solution, triethanolamine dodecyl sulfate, polyoxyethylene fatty acid ester, and 3-aminopropyltrimethoxysilane is 11.0:100:1.2:0.8:1.3.
[0097] 5. React
[0098] Add 204 mL of 16 wt% glucose solution and 0.60 g of catalyst to the reaction container, replace the gas in the reaction container with hydrogen three times, and then introduce hydrogen for stirring reaction. Control the reaction pressure to 4.2 MPa, the stirring speed to 607 rpm, the reaction time to 4.2 h, and the reaction temperature to 125 ° C. After the reaction is completed, the reaction liquid is obtained, cooled and filtered, and the filtrate is sampled and analyzed.
[0099] Sorbitol was prepared by the method of Example 3. After sampling and analysis of the filtrate, the conversion rate of glucose was 99.67% and the yield of sorbitol was 94.49%.
[0100] Comparative Example 1
[0101] Based on Example 1, the changes are that the steps of preparing mercapto activated carbon and oxidation are omitted;
[0102] In the loading step, the sulfonated activated carbon was replaced by an equal amount of alkali-leached activated carbon;
[0103] The rest of the operations are the same.
[0104] Sorbitol was prepared by the method of Comparative Example 1. After sampling and analysis of the filtrate, the conversion rate of glucose was 84.23% and the yield of sorbitol was 76.02%.
[0105] Comparative Example 2
[0106] Based on Example 1, the changes are as follows:
[0107] (1) In the loading step, the preparation step of the functionalized silica is omitted; the functionalized silica is replaced by an equal amount of untreated silica, wherein the particle size of the silica is 210 nm;
[0108] (2) In the loading step, an equal amount of sodium dodecylbenzene sulfonate was replaced with deionized water;
[0109] The rest of the operations are the same.
[0110] Sorbitol was prepared by the method of Comparative Example 2. After sampling and analysis of the filtrate, the conversion rate of glucose was 86.52% and the yield of sorbitol was 79.16%.
[0111] Catalyst performance testing
[0112] 1. Recycling performance
[0113] The catalysts in Examples 1-3 and Comparative Examples 1-2 were recovered and reused. The recovery method was as follows: the reaction solution obtained in the reaction step was cooled, and then vacuum filtered to obtain a filter cake, the filter cake was washed with deionized water for 3 times, dried at 120°C, and naturally cooled to room temperature after drying, and heated to 350°C at a rate of 2.0°C / min, and calcined at 350°C for 3.0h in an oxygen atmosphere. After calcination, the temperature was naturally restored to room temperature, and then reduced in a hydrogen atmosphere at a heating rate of 2.5°C / min, and the temperature was raised to 400°C for 4.0h. After reduction, the catalyst was naturally cooled to room temperature to obtain a regenerated catalyst.
[0114] The number of recycling applications was 26 times, and the catalyst was recycled after each reaction step. At the 26th application, the filtrate was sampled and analyzed again, and the analysis results are as follows:
[0115]
[0116] 2. Stable performance
[0117] The catalysts prepared in Examples 1-3 and Comparative Examples 1-2 were first placed under a pressure of 600 W / m 2The reaction step was then carried out, and the filtrate after the reaction was sampled and analyzed. The analysis results are as follows:
[0118]
[0119] The present invention performs mercapto treatment on activated carbon, wherein the pretreatment agent mainly plays a role of surface dispersion, reduces the agglomeration of activated carbon, and enhances the dispersion performance, and then uses a silane coupling agent to treat, so that the surface of the activated carbon contains mercapto groups, and after oxidation, the mercapto groups are fully oxidized to sulfonic acid groups. In the loading step, the porous structure of the activated carbon can load the metal components, and the dispersion degree of the metal components on the sulfonated activated carbon is high, and the loading is more uniform, so that the catalytic activity can be better exerted. Functionalized silica is also added in the complex step. The functionalized silica obtained by specific dispersion treatment and silane treatment is rich in amino groups, and It appears as separately dispersed particles. Under the action of sodium dodecylbenzene sulfonate, the amino groups of the functionalized silica can effectively interact with the sulfonic acid groups of the sulfonated activated carbon to form acid-base hydrogen bonds, thereby coating a layer of silica on the surface of the sulfonated activated carbon. The amino groups of the functionalized silica have good binding properties with the reactant glucose, which promotes the full progress of the reaction. The sulfonic acid groups and amino groups have good compatibility in the glucose solution, which enhances the catalytic stability of the catalyst and reduces the loss of metal components during the reaction, so that the catalyst still has good catalytic performance after multiple recycling and strong ultraviolet irradiation.
[0120] Comparative Example 1 omits the thiol treatment and oxidation steps of the activated carbon. On the one hand, the alkali-leached activated carbon has poor dispersibility, which makes the loading of the metal components uneven and the dispersion low in the loading step, thereby affecting the catalytic performance during the reaction and reducing the yield of sorbitol and the conversion rate of glucose. On the other hand, the alkali-leached activated carbon has poor binding properties with silica, resulting in poor homogeneity of the prepared catalyst, which ultimately greatly shortens the service life of the catalyst.
[0121] In Comparative Example 2, the functionalization treatment of silica was omitted, and the silica was in a serious aggregation state. In the loading step, it could not be evenly coated with the sulfonated activated carbon, which affected the catalytic performance and stability of the catalyst, and ultimately affected the yield of sorbitol and the conversion rate of glucose.
[0122] Unless otherwise specified, all percentages used in the present invention are by mass.
[0123] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing sorbitol, characterized in that: The preparation method comprises the steps of alkali leaching activated carbon, preparing mercapto activated carbon, oxidation, loading and reaction; The alkali leaching activated carbon step comprises: placing the activated carbon in a sodium hydroxide solution for immersion, the immersion temperature is 90-94° C., the immersion time is 11-13 hours, and after the immersion is completed, filtering, washing and drying to obtain the alkali leached activated carbon; The step of preparing mercapto activated carbon is as follows: placing alkali-leached activated carbon in a sealed container, introducing an ethanol solution and a pretreatment agent, heating to 40-44°C at a rate of 1.4-1.6°C / min, stirring for 23-28min, then heating to 60-64°C at a rate of 0.8-1.0°C / min, stirring for 16-20min, adding 3-mercaptopropyltriethoxysilane after the soaking, heating to 73-77°C at a rate of 0.4-0.6°C / min for stirring reaction, the reaction time is 9.8-10.3h, the stirring speed is 212-226rpm, and after the reaction is completed, filtering, washing, and drying to obtain mercapto activated carbon; The pretreatment agent is a mixture of polyethylene glycol monolaurate, dimethyl silicone oil and octadecyltrimethylammonium bromide; The oxidation step comprises mixing the mercapto activated carbon with a hydrogen peroxide solution, performing ultrasonic treatment, stirring after the ultrasonic treatment, the stirring time is 23-25 hours, the stirring speed is 413-425 rpm, and after the stirring is completed, drying at 78-82° C. for 6.7-7.2 hours to obtain the sulfonated activated carbon; The loading step comprises adding nickel nitrate hexahydrate to deionized water, stirring evenly, adding sulfonated activated carbon and sodium dodecylbenzene sulfonate, stirring at 393-406 rpm for 7.8-8.2 hours, adding functionalized silica after the stirring is completed, heating to 51-55° C. and stirring for 2.8-3.2 hours, filtering, washing, and drying, and then reducing under a hydrogen atmosphere to obtain a catalyst; The preparation method of the functionalized silica comprises placing silica in a sealed container, introducing a 36-40wt% ethanol solution, adding triethanolamine dodecyl sulfate for a first ball milling treatment, adding fatty acid polyoxyethylene ester and 3-aminopropyltrimethoxysilane after the ball milling, raising the temperature to 72-76° C., performing a second ball milling treatment, stirring and reacting for 6.3-6.7 hours, filtering, washing and drying after the stirring and reaction, and obtaining the functionalized silica; The reaction steps are: adding 14-16wt% glucose solution and a catalyst into a reaction container, and stirring and reacting under a hydrogen atmosphere; The volume mass ratio of the 14-16wt% glucose solution and the catalyst is 195-204mL:0.57-0.60g.
2. A method for preparing sorbitol according to claim 1, characterized in that: In the alkali leaching step, the particle size of the activated carbon is 220-240 nm, and the specific surface area is 605-614 m 2 / g; The mass concentration of the sodium hydroxide solution is 14-17%; The mass ratio of the activated carbon to the sodium hydroxide solution is 10-14:95-123.
3. A method for preparing sorbitol according to claim 1, characterized in that: In the step of preparing mercapto activated carbon, the mass concentration of the ethanol solution is 42-45%; In the pretreatment agent, the mass ratio of polyethylene glycol monolaurate, dimethyl silicone oil and octadecyltrimethylammonium bromide is 1.4-1.6:0.6-0.8:0.8-1.2; The mass ratio of the alkali-leached activated carbon, the ethanol solution, the pretreatment agent, and 3-mercaptopropyltriethoxysilane is 8.2-8.6:95-100:1.3-1.5:0.8-1.
0.
4. A method for preparing sorbitol according to claim 1, characterized in that: In the oxidation step, the ultrasonic treatment has an ultrasonic time of 13-18 min, an ultrasonic power of 140-154 W, and an ultrasonic frequency of 43-47 kHz; The mass concentration of the hydrogen peroxide solution is 30-34%; The mass ratio of the mercapto activated carbon to the hydrogen peroxide solution is 7.3-7.7:52-56.
5. A method for preparing sorbitol according to claim 1, characterized in that: In the loading step, the mass volume ratio of the deionized water, nickel nitrate hexahydrate, sulfonated activated carbon, sodium dodecylbenzene sulfonate, and functionalized silica is 73-77 mL: 1.8-2.2 g: 3.2-3.5 g: 0.07-0.09 g: 1.8-2.2 g.
6. The method for preparing sorbitol according to claim 1, characterized in that: In the loading step, the reduction is carried out by heating the temperature to 265-275°C at a rate of 2.6-3.4°C / min, keeping the temperature at 265-275°C for 18-22 minutes, then heating the temperature to 405-415°C at a rate of 1.7-2.3°C / min, keeping the temperature at 405-415°C for 4.4-4.6 hours, and then naturally returning to room temperature after the insulation is completed to obtain a catalyst.
7. The method for preparing sorbitol according to claim 1, characterized in that: In the preparation method of the functionalized silica, the particle size of the silica is 205-215 nm; The mass ratio of the silicon dioxide, the ethanol solution, the triethanolamine dodecyl sulfate, the polyoxyethylene fatty acid ester and the 3-aminopropyltrimethoxysilane is 10.7-11.0:95-100:0.8-1.2:0.6-0.8:1.0-1.
3.
8. A method for preparing sorbitol according to claim 1, characterized in that: In the preparation method of the functionalized silica, the first ball milling has a ball milling time of 23-27 min, a ball milling speed of 113-125 rpm, and a ball-to-material ratio of 3-5:1; The secondary ball milling has a ball milling time of 33-37 min, a ball milling speed of 204-215 rpm, and a ball-to-material ratio of 4-6:
1.
9. A method for preparing sorbitol according to claim 1, characterized in that: The reaction steps are as follows: adding 14-16wt% glucose solution and a catalyst into a reaction container, replacing the gas in the reaction container with hydrogen for 3 times, then introducing hydrogen for stirring reaction, controlling the reaction pressure to be 3.8-4.2MPa, the stirring speed to be 590-607rpm, the reaction time to be 3.9-4.2h, the reaction temperature to be 120-125°C, obtaining a reaction liquid after the reaction is completed, cooling and filtering, and sampling and analyzing the filtrate.
Citation Information
Patent Citations
Catalyst for preparing sorbitol and sorbitol preparation method
CN118384898A
Catalyst for synthesizing sorbitol as well as preparation method and application thereof
CN112044433A
Preparation method of sorbitol
CN117603009A